Meningkatkan Keterampilan Mencuci Pakaian Melalui Multi Metode Pada Anak Tunagrahita Mampu Latih - Shinta Neldinda; Irdamurni Irdamurni (Universitas Negeri Padang, 2020)
This study discusses the improvement of children's laundry skills tunagrahita able to train. Unskilled children washing clothes. The objective of the study was to prove that multi-methods effectively improve the washing skills of children's tunagrahita are able to train. The research used experimental type of single subject research (SSR) design A-B-A.Baseline (A) research results before treatment were given for 5 meetings with mean of 27%, direction tendency and change of horizontal data. The intervention condition (B) of multi-method treatment during 8 times meeting with mean 70.5%, direction tendency and data changes increase. The baseline condition (A2) is no longer treated for 5 meetings with mean 89.2%, direction tendency and data changes increase. Overlape data has a low percentage. In conclusion multi methods can improve the skills of children's washing tunagrahita able to train